PENERAPAN FUNGSI KERJA DAN NILAI ORGANISASI PADA TINGKAT KEPERCAYAAN MASYARAKAT - Utomo, Kurniawan Prambudi (Fakultas Ekonomi Universitas Islam 45, 2019)
This research is related to a program that regulates good governance (good governance) with the application of transparent and accountable budget management principles to increase public participation in Bekasi City, while this study aims to discuss performance-oriented, employment variables the same and increase community expectations and answer this research regarding direct conversations to respondents who are in the field using data collected using questionnaires and a list of questions that have been done compiled using a privately managed mode, the questions asked are questions that are asked directly face-to-face for respondents in this case is the City of Bekasi government in the budget and community, so the level of questionnaire questions (response rate) is 100%, while the number of respondents is 90 people and carried out in September-November 2016 results from this research, positive and good budget workers can be known. While performance evaluation gets a negative response, this is related to the government budget increase, the Bekasi City Government is very much needed to get community support and participation. Keywords: Work function, Performance Assessment, Community Assessment Level